Adaptabilidad constructiva: prototipo técnico constructivo para la vivienda de emergencia en desastres naturales por sismo y precipitaciones altas (2023)
Colombia suffers from emergencies due to various circumstances, one of which is caused by natural disasters caused by winter and the earthquakes that occur throughout the country. In the last decade, this has left a considerable number of affected families who have to leave their homes or lose them. , it has been sought that through emergency housing, which is a solution that occurs in the short term or temporarily, to face this problem of habitability.